Kibbutz - White, Alan, 1924- (London Pan Books Ltd., 1970)
The Kibbutz attempted in a small way to create a Jewish utopia based upon the tenets of equality, Jewish labor, and Zionism. This institution is examined in light of today's new developments, social changes, and economic imperatives.
Include Epilogue
Keywords: English literature